Territory and Democratic Politics A Critical Introduction - Mazzoleni, Oscar (Palgrave Studies in European Political Sociology, 2024)
Borders, democratic legitimacy, multiscale statehood, governance : the covid crisis has shaken things up and emphasized both the contradictions and the central salience of territories. In this sharp volume Oscar Mazzoleni critically reviews the main debates about territories that have unfold over the last two decades, in particular in geography and political sociology. He makes a powerful insight for a critical territorial approach aiming to analyze democratic politics. Patrick Le Galès, CNRS research professor at Sciences Po, Paris, France Mazzoleni has contributed a brief but encompassing study of the concept of territory in social sciences. This well-written piece analyzes the concept of territory as multidimensional and interdisciplinary. His is a rigorous attempt to offer a systematic framework to make territorial politics part of the contemporary research agenda. In developing a territorial approach, he adds to the field by addressing essential gaps in the literature. Margarita Gomez-Reino Cachafeiro, full professor at the UNED University, Madrid, Spain The book provides a comprehensive and up-to-date introduction to the uses of the concept of territory in the study of democratic politics. The author tests the limits of a literature which avoid territorial dimensions, and reasserts the relevance of the concepts of territory and territorial space in the understanding of contemporary politics. With a political sociological perspective, but engaging in an interdisciplinary dialogue, the book draws a new conceptual framework focusing on both traditional and innovative topics: state-building and the transformation of nation-states, the changes in democratic citizenship, the relevance of territory for voting behaviour, the territorial dimensions of populism and the experience of the pandemic, taken as a global territorial crisis. Oscar Mazzoleni is Directorof the Research Observatory for Regional politics at the University of Lausanne, Switzerland.